PENERAPAN KOMUNIKASI MASSA TERHADAP BUDAYA MASYARAKAT PADA REMAJA DI ERA SOCIETY 5.0 - Mustofa, Muhammad Bisri; Wuryan, Siti; Tari, Iis Liana; Septiani, Julisa; Andriyani, Lisa (KOMUNIKASIA: Journal of Islamic Communication and Broadcasting, 2022)
The condition of social media is now able to fully encourage social interaction and all community activities. The influence of mass communication (cognitive, affective, and behavioral) for users or social media audiences where their behavior has been positively and negatively influenced. This condition is very concerning because the socio-culture of teenagers has been influenced by the mass media which seems to have become the basic need of teenagers. The mass media should be consumed according to need, in fact now the mass media has become a basic need that has been able to fulfill and assist all daily activities. However, as a teenager in his time, he should still be controlled and need supervision. This study focuses on how the influence/effect of mass communication on audiences who use social media on teenagers in the 5.0 era of society. Adolescence is the start of the change between childhood and adulthood, which is still influenced by the mass media in this 5.0 era of society. Researchers used library research methods using various library sources or previously written works. From the results of this study, the greatest effect of social media on adolescents is a change in attitudes and behavior in the social and cultural sphere. Therefore, the social effects of mass communication on teenagers are like 2 sides of a coin that have good and bad effects, so due to the mass media today, everything that teenagers do sometimes cannot be controlled and still cannot be considered good or bad for themselves.